Microbiome Analysis Investigating the Impacts of Fermented Spent Mushroom Substrates on the Composition of Microbiota in Weaned Piglets Hindgut - Qi, Qien; Peng, Qiaoli; Tang, Min; Chen, Dongling; Zhang, Huihua (Frontiers in Veterinary Science, 2020)
The purpose of this study was to investigate the effects of Fermented Spent Mushroom Substrates (FSMS) on growth performance, serum biochemical, gut digestive enzyme activity, microbial community, genes expression of tight junction proteins and volatile fatty acids (VFAs) in hindgut (colon and cecum) of weaned piglets. A total of 100 weaned Yihao native pigs (Native × Duroc, 50 males and 50 females) were allocated to two groups with five replicates and ten pigs per replicate. Pigs in the control group were fed a basal diet (BD group) and the others were fed basal diets supplemented with 3% FSMS (FSMS group). Relative to the BD Group, it had better results for final weight, average daily gain (ADG) and feed conversion ratio (FCR) in FSMS Group but not significant (p > 0.05) which was accompanied by improved serum triiodothyronine (T3), immunoglobulin G (IgG) and immunoglobulin A (IgA) (p < 0.05) but lower serum total protein (TP), albumin (ALB), total cholesterol (TC) and total triglyceride (TG) during the overall period (p < 0.05). Similarly, FSMS significantly up-regulated (p < 0.05) the mRNA expression of duodenal tight junction proteins such as tight junction protein 1 (TJP1), tight junction protein 2 (TJP2) and occludin (OCLN). Meanwhile, isobutyric acid, valeric acid and isovaleric acid levels were increased while propanoic acid was decreased (p < 0.05) in the FSMS group than the BD group. In addition, the piglets in FSMS group changed the microbial diversity in the colon and cecum. 16S rRNA gene sequencing-based compositional analysis of the colonic and cecal microbiota showed differences in relative abundance of bacterial phyla (Firmicutes, Bacteroidetes etc.), genus (Lactobacillus, Streptococcus, Roseburia etc.) and species (Lactobacillus gasseri, Clostridium_disporicum etc.) between the BD and FSMS fed piglets. In conclusion, dietary supplementation with FSMS benefited to the intestinal mucosal barrier, immunity, and composition of microbiota.